ANALISIS DUE PROFESSIONAL CARE, TIME BUDGET PRESSURE DAN SPESIALISASI AUDITOR TERHADAP KINERJA AUDITOR - Kristianto, Giovanny; Istiningrum, RR Farida (Applied Research in Management and Business, 2024)
This study aims to determine the influence from within the auditor and also from outside the auditor. Basically, auditors in their work need financial reports that have been prepared by their clients. In working, auditors need to adhere to principles that are adjusted to the code of ethics of the public accountant profession so as not to violate existing rules in order to provide maximum performance. The basis for examining financial reports is financial accounting standards. There are factors that can influence the work of an auditor, namely due professional care, time budget pressure and auditor specialization. This study took respondents from public accounting firms in Semarang City. Testing was carried out using multiple linear regression analysis with preliminary testing such as classical assumption tests and data quality tests. Partial testing provides results that due professional care and time budget pressure have a strong influence on the performance of an auditor but have no influence from the auditor's specialization factor.